Pavel Turner in literarno ustvarjanje Josipa Vošnjaka - Cvirn, Janez (Studia Historica Slovenica, 2001)
Dr Pavel Turner, who foresaw the major route to cultural-national emancipationin education and up-bringing, was convinced that Slovenes need 'a healthy and vigorous literature' and not 'nihilism'. Thus, he opposed the sentimentalism of Josip Stritar and was a determined adversary of the Slovene modern literature movement (particularly of Cankar), which he considered to be an immature and undigested literary importation. In accordance with this, he considered (beside Jurčič and Aškerc) Josip Vošnjak to be a pinnacle in writing, whose literary endeavours he followed attentively and held in the highest esteem
Keywords: Literarna zgodovina; Literarno ustvarjanje; NUK; Slovenski književniki; slovenski pisatelji; Turner, Pavel; Vošnjak, Josip